Synchronized proxy‐based temperature reconstructions reveal mid‐ to late Holocene climate oscillations in High Arctic Svalbard. (8th November 2017) - Luoto, Tomi P.; Ojala, Antti E. K.; Arppe, Laura; Brooks, Stephen J.; Kurki, Eija; Oksman, Mimmi; Wooller, Matthew J.; Zajączkowski, Marek
ABSTRACT: Existing paleoclimate data are exceedingly sparse from southern Spitsbergen, a High Arctic region predicted to experience significant environmental changes because of amplified warming. We analyzed biotic and isotopic paleolimnological proxies to reconstruct past climate from a lacustrine sediment core, with a basal age of ∼5500 a BP, in southern Spitsbergen (77°N). We used fossil Chironomidae assemblages to quantitatively reconstruct past mean July air temperatures and stable oxygen isotope values (δ 18 O) of these fossils to estimate changes in mean annual air temperature. These proxy records are strikingly similar and show that the coldest anomaly since the mid‐Holocene occurred between 350 and 50 cal a BP, during the 'Little Ice Age', whereas the warmest period in the summer temperature record occurred between 5500–5000 and ∼2000 cal a BP . Our findings indicate that the natural long‐term air temperature dynamics in our study area are most likely connected to solar minima and positive feedback mechanisms from sea‐surface temperature maxima. The results also highlight that the recent temperature increase is unprecedented in its rate with a ∼2 °C increase in the summer temperatures during the past ∼50 years.